Determinants Influencing Alumni of Darul Huda Mayak Islamic Boarding School in Purchasing Halal-Labeled Cosmetic Products - Aryan Nurhuda; Endah Setyowati (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2025)
Introduction: This study aims to analyze the factors that influence the decision to purchase halal-labeled cosmetic products by alumni of the Darul Huda Mayak Islamic Boarding School, including halal awareness, religiosity, product safety and social environment. Research Methods: The research uses a quantitative approach with data collection through questionnaires from 96 respondents selected using stratified random sampling. Data analysis was conducted using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. Result: The findings indicate an R-square value of 0.708, suggesting that the variables in this model contribute 70.8% to the purchase decision of halal-labeled cosmetic products, while the remaining 29.2% is influenced by other variables not included in this study. The results further reveal that halal awareness and religiosity have a positive and significant effect on purchase decisions. Product safety has a positive but not significant effect, while the social environment has a negative and significant effect on the decision to purchase halal-labeled cosmetic products. These findings suggest that individual factors, such as awareness and religiosity, play a more dominant role in influencing purchase decisions than external factors. This study highlights the importance of strengthening personal values in promoting the consumption of halal products, especially among Muslim consumers.